THE DISPOSITION EFFECTS ON THE FINANCIAL CRISIS OF THE INDONESIAN CAPITAL MARKET - Rohmad Fuad Armansyah (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2018)
Disposition effects can be positive but can also have a negative impact on capital market activity. Positive if the behavior of selling or holding the assets is done after obtaining enough information on the investments, so that the market becomes dynamic, in the contrary, it will be negative if the behavior of selling / holding the assets by investors on the basis of not wanting to lose or because of the expectations in the future could lead to destruction or financial crisis. These behavior in some research causing the market unstable while other did not find disposition appear in their market. This research is to examine whether there is a behavior of the disposition effect before the crisis, during the crisis, and after the financial crisis of 2013 on the Indonesian capital market. The data of LQ45 group companies are used in this study with 810 obser-vations as the data of disposition effect base on investor trading through brokerage firm. The results show that there is no disposition effect behavior in financial crisis especially as what happened in Indonesia in 2013